The Impact of Inter-provincial Migration on the Labor Market Outcomes in Two Developed Provinces in South Africa - Kleinhans, Joseph; Yu, Derek (African Human Mobility Review, 2021)
This study used the South African Census 2011 data to examine the impact of interprovincialmigration on the labor market outcomes in the Western Cape and Gauteng,the two most developed and popular inter-provincial migration destination provincesin South Africa. In both provinces, the residents were divided into four groups: permanentresidents, intra-provincial migrants, long-term inter-provincial migrants andshort-term inter-provincial migrants. The descriptive statistics indicated that bothshort- and long-term inter-provincial migrants into the two provinces were likely tobe young people aged 15-34 years, unmarried African urban residents with 11-12 educationalyears on average, coming from households with three members. These interprovincialmigrants enjoyed lower unemployment rates than the permanent residents,but the intra-provincial migrants remained the best-performing group with the lowestunemployment rate and highest share of employed persons involved in formal sectoractivities. The study also conducted a multivariate econometric analysis with probitregressions on labor force participation likelihood, and Heckprobit regressions on employmentlikelihood (conditional on labor force participation). After controlling fordifferences in other characteristics (or ceteris paribus), compared to the permanentresidents, it was evident that both short- and long-term inter-provincial migrants intoWestern Cape and Gauteng were about 3% significantly more likely to be employed.After examining migrants from the Eastern Cape to the Western Cape and migrantsfrom Limpopo to Gauteng, the study found that both groups enjoyed a much higherlabor force participation rate (above 70%) and lower unemployment rate (30%), comparedto individuals who remained in the Eastern Cape and Limpopo (labor force participationrate: 45%; unemployment rate: 38%).